Evaluation of a Few Locally Available Anaesthetics for Potential Use in Fish Seed Transportation - U.C., Goswami; S.K., Das (Fishery Technology, 2025)
A study was conducted to explore the possibility of using a few locally available anaesthetics, thiopentone sodium, xylodac, lignocaine and sodium chloride for fish seed transportation. Application was made by inhalation of anaesthesia where by the drugs, in aqueous solution, entered the arterial blood during ventilation of the gills. The study revealed that the mixed seeds of major carp (Labeo rohita, Cirrihinus mrigala and Catla catla) of average length 2.8 cm could be transported safely in a solution containing thiopentone sodium @15 mg/L of water for more than 30 min without oxygen. In the case of lignocaine, lOml/L gave the best result with a recovery time of 14 min; whereas, 4ml/L of xylodac was found to be effective for fish fry with a mean survivability of 90%. The anaesthetics were found to reduce the activity of the fish fry in the aqueous solutions of the sedative agents. The study indicates the possibility of utilizing these compounds for short duration fish seed transportation.